PENCEMARAN PLASTIK DI LAUT - Muhammad Reza Cordova (Pusat Penelitian Oseanografi LIPI, 2017)
PLASTICS POLLUTION IN THE SEA. Indonesia is considered as the second biggest plastic waste producer in the sea. Information on waste pollution and its impact on marine organisms in Indonesia is still limited. Waste disposal and solid waste (plastics) into the sea are continuously occuring; elevating the thoughts of global impact of plastic waste contamination. Increased use of plastic is a consequence of the development of technologies, industries and also the population. This paper is expected to provide knowledge and information of plastics that exist in the sea, especially Indonesian Sea.